Reconceptualising the Post-peasantry: Household Strategies in Mexican Ejidos - Schüren, Ute (European Review of Latin American and Caribbean Studies, 2003)
In his widely discussed book Micheal Kearney (1996) questions the peasant concept in anthropology. Current global conditions, he argues, do not favour the perpetuation of the peasantry. Therefore, this category should be abandoned. Instead, Kearney proposes to call the globalised postpeasant individuals polybians. Because they carry out different economic strategies they are slippery creatures, defy social bounds, and have multiple social identities. Kearney is right in criticising the essentialism of earlier approaches. However, his concept runs the risk of establishing a new essentialisation. I will argue against the point forwarded by Kearney and many others that recent trends in globalisation have resulted in radical new household strategies of rural people. Historical and ethnographical data of rural communities (ejidos) the Chenes region on the central Yucatan peninsula, Mexico illustrate that the rural economy has changed constantly – sometimes slowly, sometimes radically – including processes of occupational multiplicity, wage labour and migration. People adopted new or revived former economic strategies in response to changing local, regional, national and global processes. There was no unilinear sequence from peasant to migrant. During the ‘golden years’ of chicle exploitation in the 1930s and the early 1940s, for example, many peasants became wage labourers in the chewing gum industry. Later, a peasantisation process developed due to the bust of the chicle economy and increasing prices of corn. Resumen: Reconceptualizar lo post-campesino: estrategias domésticas en los ejidos mexicanosEn su libro ampliamente discutido, Micheal Kearney (1996) cuestiona el concepto ‘campesino’ en la antropología. Las condiciones globales de hoy en día, argumenta Kearney, dificultan la perpetuación de ‘lo campesino’. Por lo tanto, esta categoría debe entrar en desuso. En su lugar, Kearney propone llamar polybians a los post-campesinos globalizados. Ya que ellos son criaturas inaprensibles al desarrollar diferentes estrategias económicas, desafían límites sociales y tienen múltiples identidades sociales. Kearney está en lo cierto al criticar el esencialismo presente en perspectivas anteriores. Sin embargo, su concepto corre el riesgo de convertirse a su vez en un esencialismo. Yo discuto sobre la perspectiva que Kearny y otros autores proponen al decir que el rumbo reciente de la globalización ha producido estrategias domésticas radicalmente nuevas entre la gente rural. Datos históricos y etnográficos de las comunidades rurales (ejidos) de la región chen en el centro de la península de Yucatán, México, ponen de manifiesto que la economía rural ha estado en constante cambio – algunas veces lentamente, otras más intensamente-, visible a través de procesos de ocupación múltiple, trabajo asalariado y migración. La gente ha revitalizado o creado estrategias económicas en respuesta a cambiantes procesos locales, regionales, nacionales y globales. No ha habido una trayectoria lineal en la transición de campesino a migrante. Por ejemplo, durante la llamada ‘época dorada’ de la extracción de chicle de 1930 hasta comienzo de la década de 1940, muchos campesinos se convirtieron en trabajadores asalariados en la industria de la goma de mascar. Tiempo después, los trabajadores se volvieron campesinos, debido a la quiebra de la economía del chicle y el incremento en los precios del maíz.